Dirichlet problem and non uniquely solvable Reimann - Hilbert problem via boundary integral equation with corners - Munira Ismail, author; Ali Hassan Mohd Murid, author; Bahrom Sanugi, author; International Journal of pure and Applied Mathematics (2006 : Johor) (Skudai : Universiti Teknologi Malaysia, 2006)
PRZSL